PLANEJAMENTO DOS RECURSOS HÍDRICOS: ANÁLISE DA QUALIDADE DEMOCRÁTICA COM FOCO NA DIVERSIDADE DOS PARTICIPANTES - Barbosa, Adriane Oliveira Santos (2019)
This study begins from one of the great challenges of the National System of Water Resources Management (Sistema Nacional de Gerenciamento de Recursos Hídricos - SINGREH), to promote social participation, especially of the civil society and of the users of the SINGREH, in the elaboration of basin plans. The general objective of this work was to analyze the democratic quality of the water resources planning processes in relation to the participating actors and segments. The object of analysis was the elaboration process of the Framing of Water Bodies and the Water Resources Plan in the water basins of the “Jucu” and “Santa Maria da Vitória” rivers in Espírito Santo state, Brazil. The analysis of the democratic quality of this participatory process focused on the criterion "diversity of participants". In addition to the authors who approach participatory democracy in Brazil in the perspective of power sharing, this study was also based on the foundations of Law 9.433/1997, which instituted the Water Resources National Policy; the resolutions of the Water Resources National Council, which deals with Framing of Water Bodies and Water Resources Plan; the recommendations of international organizations; and the elements of the democratic quality of participatory processes. This is a qualitative research developed through bibliographical studies and analysis of documents related to the process in perspective, and also through interviews with strategic actors that followed the process. The research concluded that the participatory mapping of basin strategic actors and the social mobilization plan did not guarantee the expected attendances, not even the members of the committees attended the various events. As a result, emptying of public meetings, as well as low representation, especially of users and communities, were observed. In general, there was the dispersion of the participants and the lack of interest of the population. The absences and the lack of representativeness of the strategic actors of the basin call into question the very essence of a water resources plan: the construction of a collective pact on water management. The need to intensify processes of social mobilization and of social and technical learning for managers, technicians, basin committees, and for society itself is thus verified, so that everyone feels properly responsible for the water resources management. We hope to contribute to the improvement of the democratic quality of the participatory processes of water resources planning through this work.